Scatter correction in Tc99m SPECT using effective attenuation coefficient and material filter technique - Sayed, Inayatullah Shah; Muda, Siti Zubaidah (2012)
Single Photon Emission Computed Tomography (SPECT) is one of the diagnostic imaging modality that has been increasingly used since last couple of decades for the diagnosis of diseases. SPECT uses the gamma emitting radionuclides labeled with a suitable pharmaceutical; small quantity is introduced into the patient’s body. Gamma photons emanating from the target organ/patient’s body are detected externally by gamma camera. Unfortunately, SPECT suffers the scatter problem that degrades the image quality and compromise its utility in clinical examinations. Scatter issue has been addressed by a number of researchers by developing scatter correction techniques. In this study, effective attenuation coefficient and material filter technique has been applied in order to correct the scatter. A new emission tomography phantom provides similar transverse view of cold and hot regions was scanned. Phantom was filled with water and 20mCi of Tc99m radioactivity was evenly distributed. Philip ADAC Forte dual head gamma camera installed with LEHR collimator was used. Standard symmetric energy window (±10%) centred at 140 keV was selected. Material filter (absorber sheet) was mounted on the outer surface of the collimator - aluminum (thickness 0.3 mm). Image data were acquired without and with material filter (absorber sheet). Filtered back projection image reconstruction technique was used by selecting Butterworth mathematical filter with cut-off frequency 0.35 cycles/cm order 5. Chang’s attenuation correction technique was also applied. Hot and cold region images were qualitatively and quantitatively analyzed. Detectability of both types of regions and contrast was investigated. Standard deviation in the count density of uniform region was measured. Results show the improvement in detectability and contrast of hot and cold regions with material filter. Also noise component in the uniform images has been reduced with the material filter as compared to the use of effective attenuation coefficient. It is concluded that, material filter technique improves image quality as compared to effective attenuation coefficient technique. Thus, for further investigations material filter technique may be applied for more complicated phantoms, i.e., anthropomorphic torso phantom, in order to find the applicability of the technique in clinical studies.